Judgemental attitudes in pastoral care : spiritual councelling for women living positively with HIV and AIDS in the township of Lwandle - Matholeni, Nobuntu (Stellenbosch : Stellenbosch University, 2012)
Thesis (MTh)--Stellenbosch University, 2012.